Dominant discourses and narratives of substance use: the development of a psychometric measure of internalisation - Bright, Stephen Jason (Curtin University, 2014)
This research is comprised of four papers. The first describes the identification of six dominant discourses that frame Alcohol and Other Drugs (AOD) within Australia. The second examines the interaction between these dominant discourses with policy and AOD-related harm. The final papers describe the development of a psychometric tool that is proposed to measure the degree to which individuals internalise the six dominant discourses, which is explored using the Locus of Control of Behaviour Scale.